2007
DOI: 10.1021/ol062960h
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-Sundiversifolide

Abstract: The first, enantiocontrolled total synthesis of (+)-sundiversifolide has been accomplished using the sequential ring-closing metathesis, [3,3]-sigmatropic rearrangement, and iodolactonization for the key assembly of the cis-fused oxabicyclo[5.3.0]decene framework of the natural product. [structure: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Chemical studies of Helianthus annuus have shown that this species is a rich source of terpenes, 4) and particularly of sesquiterpenes, e.g., heliananes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and sundiversifolide (14), [5][6][7][8] with a wide spectrum of biological activities, including potential allelopathic activity. The ionone-type bisnorsesquiterpenes (15,16) 9,10) have been isolated from rattail fescue (Vulpia myuros) and identified as allelochemicals 11) and the meroterpenes breviones (17)(18)(19), isolated from Penicillium brevicompactum Dierckw, have also been identified as allelochemicals.…”
Section: Synthesis Of Natural Products With Allelopathic Activitymentioning
confidence: 99%
“…Chemical studies of Helianthus annuus have shown that this species is a rich source of terpenes, 4) and particularly of sesquiterpenes, e.g., heliananes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and sundiversifolide (14), [5][6][7][8] with a wide spectrum of biological activities, including potential allelopathic activity. The ionone-type bisnorsesquiterpenes (15,16) 9,10) have been isolated from rattail fescue (Vulpia myuros) and identified as allelochemicals 11) and the meroterpenes breviones (17)(18)(19), isolated from Penicillium brevicompactum Dierckw, have also been identified as allelochemicals.…”
Section: Synthesis Of Natural Products With Allelopathic Activitymentioning
confidence: 99%
“…Owing to the relatively limited number of reports on synthetic studies of xanthanolides, the development of an ef cient synthetic strategy is needed in order to not only supply these natural products, but also identify their biological targets and develop related drugs. 2 The RCM method has been considered as the rst choice to design a synthetic strategy for seven membered ring construction, and Morken, 3 Martin, 4 and Shishido, 5 as well as our group 6 reported the synthesis of xanthanolides using the RCM method including enyne metathesis. 7 However, developing transition metal free methodologies should be no less important than the RCM method from the perspective of natural resources issues as well as the diversity of synthetic methodologies.…”
Section: Total Synthesis Of Xanthanolidesmentioning
confidence: 99%
“…and divided into two groups according to the configuration of their cis-and trans-ring junctions. Representative examples of the cis-fused xanthanolides are the sundiversifolide (4), [7][8][9][10]11) the diversifolide (5) 10,12) and the 8-epi-xanthatin (9) 11,13,14) ; xanthatin (7) 11,15) and 11α,13-dihydroxanthatin (8) belong to the trans series. 11,16) They are known for their wide variety of interesting allelopathic, 17) cytotoxic, 18) anti-leishmanial, 19) and anti-MRSA activity.…”
Section: Multidrug-resistant Pathogens Such As Methicillin-resistantmentioning
confidence: 99%